THE EFFECT OF LEADERSHIP, WORK MOTIVATION AND WORK ENVIRONMENT OF EMPLOYEE PERFORMANCE (Case study of PT. Aneka Ilmu Semarang Section Printing) - Fani Yuli Elisiana; Hari Susanta Nugraha; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
Leadership is a very important factor for the company because of the absence of leadership a company would not be able to run well. Award motivation is also very important to always maintain and improve the company's performance. In addition to these two factors also have to be supported by the good working environment so that the convenience provided by the company can support the employee's performance.This research aims to know the effect of leadership, work motivation and work environment to employees performance at CV. Aneka Ilmu Semarang printing section. The proposed hypothesis that there is influence of the variables of leadership, motivation and work environment to employees performance at CV. Aneka Ilmu Semarang printing section. This type of research used in this research is explanatory research, the sampling technique used was simple random sampling technique that is included in the probability sampling technique with a sample of 53 respondents and the questionnaire as a research instrument. The analytical method used in this study using linear regression analysis with SPSS 17.0 for Windows.The result of this research showes that the variables of leadership has a significant effect (partially) on the performance of employees amounted to 47.4%. Work motivation has significant influence (partially) on the performance of employees amounted to 56.2%. Work environment variables have a significant effect (partial) to employee performance by 38.3%. Variable leadership, motivation and work environment have influence together (simultaneously) on the performance of employees amounted to 62.4%.Based on the research results, it is recommended that companies improve leadership, namely by improving the ability of leaders to get closer to employees. In addition, increase motivation to work can be done by improving communication with employees. The working environment can be improved by improving the existing infrastructure in the enterprise. Through this event the expected level of performance of employees at CV. Aneka Ilmu Semarang will be increased.